Β-catenin-activated hepatocellular carcinomas are addicted to fatty acids. Issue 2 (12th April 2018) - Senni, Nadia; Savall, Mathilde; Cabrerizo Granados, David; Alves-Guerra, Marie-Clotilde; Sartor, Chiara; Lagoutte, Isabelle; Gougelet, Angélique; Terris, Benoit; Gilgenkrantz, Hélène; Perret, Christine; Colnot, Sabine; Bossard, Pascale
Abstract : Objectives: CTNNB1 -mutated hepatocellular carcinomas (HCCs) constitute a major part of human HCC and are largely inaccessible to target therapy. Yet, little is known about the metabolic reprogramming induced by β-catenin oncogenic activation in the liver. We aimed to decipher such reprogramming and assess whether it may represent a new avenue for targeted therapy of CTNNB1 -mutated HCC. Design: We used mice with hepatocyte-specific oncogenic activation of β-catenin to evaluate metabolic reprogramming using metabolic fluxes on tumourous explants and primary hepatocytes. We assess the role of Pparα in knock-out mice and analysed the consequences of fatty acid oxidation (FAO) using etomoxir. We explored the expression of the FAO pathway in an annotated human HCC dataset. Results: β-catenin-activated HCC were not glycolytic but intensively oxidised fatty acids. We found that Pparα is a β-catenin target involved in FAO metabolic reprograming. Deletion of Pparα was sufficient to block the initiation and progression of β-catenin-dependent HCC development. FAO was also enriched in human CTNNB1 -mutated HCC, under the control of the transcription factor PPARα. Conclusions: FAO induced by β-catenin oncogenic activation in the liver is the driving force of the β-catenin-induced HCC. Inhibiting FAO by genetic and pharmacological approaches blocks HCC development, showing that inhibition of FAO is a suitable therapeutic approach for CTNNB1 -mutated HCC.